Analysis of the variability in the parameters of density and moisture content for sandy soils with high clay and silt content, improved with bottom ash, through proctor tests - Gabriel, Zayde Jackeline Yopan (2024)
The existence of sandy soils with high clay and silt contents in various areas of Peru represents a problem in the case of infrastructure works in general, especially in building foundation projects. The state of these soils varies depending on the humidity conditions, due to this characteristic, it does not have a good bearing capacity. It is necessary to study an improvement that allows to satisfy the stability conditions that allow them to support loads, whether they come from buildings and/or are used as foundation material for road projects, especially in a seismic country like Peru. This article evaluates the improvement of these soils with the use of bottom ash, by-products of the non-industrial manufacture of clay bricks for construction, through the analysis of the results of the Proctor Test.